Extended-release niacin increases anti-apolipoprotein A-I antibodies that block the antioxidant effect of high-density lipoprotein-cholesterol: the EXPLORE clinical trial. - Batuca, J (2017)
Extended-release niacin (ERN) is the most effective agent for increasing high-density lipoprotein-cholesterol (HDL-C). Having previously identified anti-HDL antibodies, we investigated whether ERN affected the antioxidant capacity of HDL and whether ERN was associated with the production of antibodies against HDL (aHDL) and apolipoprotein A-I (aApoA-I). METHODS: Twenty-one patients older than 18 years, with HDL-C ≤40 mg dl-1 (men) or ≤50 mg dl-1 (women) were randomly assigned to receive daily ERN (n = 10) or placebo (n = 11) for two sequential 12-week periods, with 4 weeks of wash-out before cross-over. Primary outcome was change of paraoxonase-1 (PON1) activity and secondary outcomes were changes in aHDL and aApoA-I antibodies. Clinical Trial Unique Identifier: EudraCT 2006-006889-42. RESULTS: The effect of ERN on PON1 activity was nonsignificant (coefficient estimate 20.83 U l-1 , 95% confidence interval [CI] -9.88 to 51.53; P = 0.184). ERN was associated with an increase in HDL-C levels (coefficient estimate 5.21 mg dl-1 , 95% CI 1.16 to 9.25; P = 0.012) and its subclasses HDL2 (coefficient estimate 2.46 mg dl-1 , 95% CI 0.57 to 4.34; P = 0.011) and HDL3 (coefficient estimate 2.73 mg dl-1 , 95% CI 0.47 to 4.98; P = 0.018). ERN was significantly associated with the production of aApoA-I antibodies (coefficient estimate 0.25 μg ml-1 , 95% CI 0.09-0.40; P = 0.001). aApoA-I titres at baseline were correlated with decreased PON activity. CONCLUSIONS: The rise in HDL-C achieved with ERN was not matched by improved antioxidant capacity, eventually hampered by the emergence of aApoA-I antibodies. These results may explain why Niacin and other lipid lowering agents fail to reduce cardiovascular risk.